INDEXING SCHEME USING PARTITIONED B+-TREE (ISPB) FOR IMPROVING THE EFFICIENCY OF THE HADOOP MAPREDUCE QUERY PROCESSING - ABDULLAHI, ALI USMAN (2018)
The rapid generation and accumulation of data in recent time have led to the concept of big data which requires emergent and development of tools, techniques and systems with significant performance improvement when handling such datasets. Hadoop is one of such systems, that processes 1TB of data in 2 min on a 100 nodes cluster. In an attempt to improve the Hadoop performance indexing was introduced into it.